"SEDENTARY" WOMEN AND "COQUETTES" AT THE MARGIN: deviating feminineness in Renato Kehl's works "sedentarias" y "coquettes - André Luiz dos S. Silva; Silvana Vilodre Goellner (Universidade Federal de Goiás, 2008)
The present text discusses about women marginalized by the normative and disciplinary discourse by Renato Kehl, one of the most important Brazilian eugenists. Among his works, we cut out the period between 1917 and 1929 to investigate how the image of deviating bodies and feminineness, together with the physical education image, is conceived. Referred to as "sedentary" and "coquettes", Kehl uses their bodies attributing to them notions of impurity, indolence, and ugliness. In counterpart to the coquette's artifices and the sedentary woman's laziness, the eugenic woman should cultivate the honest beauty by performing gymnastic exercises - her beauty should be "natural" and hygienic. Health, honesty, robustness, and beauty are attributes that have become central with the marginalization of deviating feminineness. Este texto habla sobre mujeres marginadas por discursos normativos y disciplinares proferidos por Renato Kehl, uno de los más importantes defensores de la Eugenesia brasileña. En medio a su obra, recortamos el período entre 1917 y 1929, investigando, juntamente con la educación física, la imagen  femenina con desvío. Referidas como "sedentarias" y "coquettes", Kehl utiliza sus cuerpos atribuyéndoles nociones de impureza, indolencia y fealdad. En contrapartida a las  artimañas de las "coquette", y a la pereza de la sedentaria, la  mujer eugenesia debe cultivar la belleza honesta por medio de los ejercicios gimnásticos - su belleza debe ser "natural" y higiénica. Salud, honestidad, robustez y hermosura son predicados que se tornaron centrales con la marginalización de femenina con desvíos. Este texto fala sobre mulheres marginalizadas por dizeres normativos e disciplinares proferidos por Renato Kehl, um dos mais importantes eugenistas brasileiros. Em meio a sua obra, recortamos o período entre 1917 e 1929, para investigarmos como gesta, juntamente com a educação física, a imagem de corpos e feminilidades desviantes. Referidas como "sedentárias" e coquettes, Kehl utiliza seus corpos atribuindo-lhes noções de impureza, indolência e feiúra. Em contrapartida às artimanhas das coquette, e à preguiça da sedentária a mulher eugênica deve cultivar a beleza honesta por meio dos exercícios ginásticos - sua beleza deve ser "natural" e higiênica. Saúde, honestidade, robustez e formosura são predicados que se tornaram centrais com a marginalização de feminilidades desviantes.